(untitled) (Baghdad Science Journal, 2014)
Thirty clinical isolates of Helicobacter pylori bacteria obtained from patients attending endoscopy unit of Ibn-Sena teaching hospital in Mosul . These patients were complaining from epigastric pain , dyspepsia , acidity , vomiting , abdominal pain , flatulance , heart burn and melena . The H. pylori isolates were used for Haemagglutination assay (HA) , which involves the recognition of various glycoconjugates on the surface of red blood cells . In this study sheep red blood cells has been used in (HA) assay because the sheep erythrocytes surface resemble that of human epithelial cells . The results proved by (HA) assay, the ability of H. pylori to adherence to specific receptors on the surface of Human Epithelial Cell , which is the first step in the pathogenic process .